Worst friends : Thomas Jeffeson, John Adams and the true story of an American feud - Jurmain, Suzanne Tripp (New York : Scholastic, 2011)
This is the story of two of America's most well-known presidents and how they learned to put their political differences aside for the sake of friendship.